The value of time in the contract of transactions in Islamic jurisprudence - Mohammed, Alhadi AbdAllah Alhsan (Journal of Islamic Sciences, 2019)
This study entitled The Status of Time in Islamic jurisprudence (‘fiqh’) aims at showing the relation of time to price in contracting and the effect of time in contracts in terms of validity or invalidity and the place of the time of the contract whether negatively or positively and its limits. The study employs the descriptive and inductive approach. The research mainly concluded that time has no status in contracts in Islamic jurisprudence and thatbinding price to passage of time is usury itself. The main recommendation of the study is that the phrase time has a part in the price be redefined by categorizing it among the legislative rules and to submit transactions to the results of the present research regarding the status of time in contracts.
Keywords: time; contract; price; sale of peace